The Sequences of Nidaros: A Nordic Repertory & Its European Context, edited by Lori Kruckenberg and Andreas Haug - Gunilla Iversen (Novus, 2009)
Among all known repertories of sequences one of the most expansive repertories in Europe is that of the cathedral in Nidaros in northern Scandinavia. From the first quarter of the thirteenth century up to 1519 Nidaros was the arch diocese of Norway, Iceland, the Orkney Islands, the Faeroe Islands, Greenland, and the Western Isles of Scotland. Before that Nidaros had been a provincial bishop's see, and since 1103 subject to the province of Lund (in medieval Denmark) formally placed under the authority of Hamburg-Bremen. Nidaros contained the shrine of St Olav (995-1030) and was the burial place for the Royal family.